The Existence of Three Positive Solutions for $p$-Laplacian Difference Equation with Delay (Communications in Mathematical Research, 2021)
In this paper, we study the multiplicity of positive solutions for a classof $p$-Laplacian difference equations with delay. We propose sufficient conditions forthe existence of at least three positive solutions and we also provide two numericalexamples to illustrate the theoretical results.